Semi-clathrate hydrate process of methane in porous media-microporous materials of 5A-type zeolites. (15th May 2018) - Zhao, Yangsheng; Zhao, Jianzhong; Liang, Weiguo; Gao, Qiang; Yang, Dong
Highlights: The pressure and temperature of hydrate formation in 5A-type zeolites is measured. The kinetics of hydrate formation is investigated at various initial pressure and promoters. The effect of promoters, namely THF and TBAB on the hydrate formation is studied in microporous materials. Abstract: Porous media can significantly promote the kinetics of hydrate formation by reducing the barrier of physical chemistry, where zeolites are typical microporous minerals. In this paper, the formation process and the reaction kinetics of the methane hydrate were investigated in A-type zeolite with tetrahydrofuran (THF) and tetra-n-butyl ammonium bromide (TBAB) aqueous solution in a long tubular reactor. The results showed that good kinetic characteristics of methane hydrate formation can be achieved with A-type zeolite. At initial pressure of 1.5 MPa and 1.8 MPa at 285.15 K, the aqueous solution of tetrahydrofuran (THF) and tetra-n-butyl ammonium bromide (TBAB) with 5A-type zeolite can form methane hydrate with gaseous methane in 10 h. The temperature raised significantly during the formation process of the system with 5A-type zeolite. Throughout the reaction, there was an obvious temperature rising region which was located in the inlet side of tubular reactor. The gas uptake increased rapidly in the beginning of 100 min and then maintained stable increasing during the hydrate formation. The final gas uptake capacity raised with the reaction pressure but was little affected by the type of promoter. From 1.5 MPa to 1.8 MPa the final gas uptake of hydrate increased 6.48% and 6.15% in the THF and TBAB solution respectively. The reaction rate quickly reached the peak after the reaction began and then rapidly dropped to decays. Simultaneously the average of reaction rate of THF solution was 13.2–30.8% higher than that of TBAB solution when the pressure was 1.5 MPa and 1.8 MPa at the same experimental conditions.